2015
DOI: 10.1016/j.aop.2015.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Magnetically charged regular black hole in a model of nonlinear electrodynamics

Abstract: We obtain a magnetically charged regular black hole in general relativity. The source to the Einstein field equations is nonlinear electrodynamic field in a physically reasonable model of nonlinear electrodynamics (NED). "Physically" here means the NED model is constructed on the basis of three conditions: the Maxwell asymptotic in the weak electromagnetic field limit; the presence of vacuum birefringence phenomenon; and satisfying the weak energy condition (WEC). In addition, we analyze the thermodynamic prop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 36 publications
(40 reference statements)
1
52
0
Order By: Relevance
“…For M = 0 , µ = 3, the solution is the Hayward black hole [9] which has been constructed in [22]. For the solution with zero Schwarzschild mass, the behavior of the metric function f and the low lying curvature polynomials are still given by (19) and (20) respectively. Thus, the regular black hole solution has µ ≥ 3 as well.…”
Section: Case 2: Hayward Classmentioning
confidence: 99%
“…For M = 0 , µ = 3, the solution is the Hayward black hole [9] which has been constructed in [22]. For the solution with zero Schwarzschild mass, the behavior of the metric function f and the low lying curvature polynomials are still given by (19) and (20) respectively. Thus, the regular black hole solution has µ ≥ 3 as well.…”
Section: Case 2: Hayward Classmentioning
confidence: 99%
“…Thermodynamic properties of regular NED BHs were discussed in [17,18,19,21,20,22,23,24], in particular, the first law of thermodynamics, heat capacity, the validity of Smarr's formula for the BH mass, etc.…”
Section: Introduction a Brief Reviewmentioning
confidence: 99%
“…Many authors studied the stability properties of NED BHs [32,33,34,35,36,20] and their quasinormal modes related to different kinds of perturbations [37,35,36,38,16] in cases where these BHs are stable. In particular, simple conditions on the NED Lagrangian have been derived, which imply linear stability in the domain of outer communication [32], and linear stability has been verified for a number of particular examples.…”
Section: Introduction a Brief Reviewmentioning
confidence: 99%
“…It is found that not only the Big-Bang singularity but also the black hole singularity can be avoided by using the non-linear electromagnetic field. Correspondingly, some regular black hole solutions without singularities are obtained [59][60][61][62][63][64][65][66][67][68][69][70]. As for the black hole horizons, the Kerr-Newman-de Sitter spacetime has at most three horizons, the inner horizon, the event horizon and the cosmic horizon.…”
Section: Introductionmentioning
confidence: 99%